1997
DOI: 10.1152/jappl.1997.82.5.1601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of supplemental oxygen on forearm vasodilation in humans

Abstract: Supplemental O2 reduces cardiac output and raises systemic vascular resistance in congestive heart failure. In this study, 100% O2 was given to normal subjects and peak forearm flow was measured. In experiment 1, 100% O2 reduced blood flow and increased resistance after 10 min of forearm ischemia (flow 56.7 +/- 7.9 vs. 47.8 +/- 6.7 ml.min-1.100 ml-1; P < 0.02; vascular resistance 1.7 +/- 0.2 vs. 2.4 +/- 0.4 mmHg.min.100 ml.ml-1; P < 0.03). In experiment 2, lower body negative pressure (LBNP; -30 mmHg) and veno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
60
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 23 publications
5
60
0
Order By: Relevance
“…The observation that hyperoxia increased vascular resistance in both groups is consistent with the findings of many investigators (2,4,6,7,11,23,28). We have made the novel observation that hyperoxic vasoconstriction is prevented by vitamin C, suggesting that hyperoxia-associated ROS are mediators of this vascular response.…”
Section: Hyperoxic Vasoconstrictionsupporting
confidence: 91%
See 3 more Smart Citations
“…The observation that hyperoxia increased vascular resistance in both groups is consistent with the findings of many investigators (2,4,6,7,11,23,28). We have made the novel observation that hyperoxic vasoconstriction is prevented by vitamin C, suggesting that hyperoxia-associated ROS are mediators of this vascular response.…”
Section: Hyperoxic Vasoconstrictionsupporting
confidence: 91%
“…Release of NO from these compounds is likely inversely related to blood O 2 tension (15). Vitamin C may thus prevent hyperoxic vasoconstriction by several mechanisms involving NO bioavailability, including direct quenching of superoxide anions, stabilization of BH 4 , and possibly increasing the release of NO from peroxynitrite and nitrosylated compounds (24).…”
Section: Hyperoxic Vasoconstrictionmentioning
confidence: 99%
See 2 more Smart Citations
“…An understanding of hyperoxic effects on the circulatory system is fundamental to the understanding of the efficacy of hyperbaric oxygen therapy in clinical situations, though the effect of hyperoxia on the skin circulation is still unclear. It has been reported that supplemental oxygen increases peripheral vascular resistance [1,2] and decreases the limb vasodilator response to forearm ischemia [3]. Since the sympathetic nerve activity to muscle is decreased or unchanged under hyperoxic conditions [4,5], this peripheral vasoconstriction may be associated with nonsympathetic mechanisms.…”
mentioning
confidence: 98%